Vpu protein of human immunodeficiency virus type 1 enhances the release of capsids produced by gag gene constructs of widely divergent retroviruses. - Göttlinger, H G (1993)
The Vpu protein of human immunodeficiency virus type 1 facilitates the release of virus particles from the surface of infected cells. The ability of the Vpu protein to facilitate release of Gag proteins from retroviruses that lack a Vpu-like protein was examined. The results of these experiments show that Vpu significantly increases the release of the Gag proteins of human immunodeficiency virus type 2, visna virus, and Moloney murine leukemia virus from HeLa cells. The results indicate that Vpu-mediated enhancement of particle release requires neither amino-terminal myristoylation of the Gag precursor nor cleavage of the Gag precursor by the viral protease. The results raise the possibility that Vpu modifies a cellular pathway common to the release of all retroviruses from the cell surface.